Task-specific enhancement of hippocampus-dependent learning in mice deficient in monoacylglycerol lipase, the major hydrolyzing enzyme of the endocannabinoid 2-arachidonoylglycerol - Kishimoto, Yasushi; Cagniard, Barbara; Yamazaki, Maya; Nakayama, Junko; Sakimura, Kenji; Kirino, Yutaka; Kano, Masanobu (Frontiers in Behavioral Neuroscience, 2015)
Growing evidence indicates that the endocannabinoid system is important for the acquisition and/or extinction of learning and memory. However, it is unclear which endocannabinoid(s) play(s) a crucial role in these cognitive functions, especially memory extinction. To elucidate the physiological role of 2-arachidonoylglycerol (2-AG), a major endocannabinoid, in behavioral and cognitive functions, we conducted a comprehensive behavioral test battery in knockout (KO) mice deficient in monoacylglycerol lipase (MGL), the major hydrolyzing enzyme of 2-AG. We found age-dependent increases in spontaneous physical activity in MGL KO mice. Next, we tested the MGL KO mice using 5 hippocampus-dependent learning paradigms (i.e., Morris water maze [MWM], contextual fear conditioning, novel object recognition test, trace eyeblink conditioning, and water-finding test). In the MWM, MGL KO mice showed normal acquisition of reference memory, but exhibited significantly faster extinction of the learned behavior. Moreover, they showed faster memory acquisition on the reversal-learning task of the MWM. In contrast, in the contextual fear conditioning, MGL KO mice tended to show slower memory extinction. In the novel object recognition and water-finding tests, MGL KO mice exhibited enhanced memory acquisition. Trace eyeblink conditioning was not altered in MGL KO mice throughout the acquisition and extinction phases. These results indicate that 2-AG signaling is important for hippocampus-dependent learning and memory, but its contribution is highly task-dependent.